Annual Reproductive Strategy of the Squirrel Monkey (Saimiri sciureus) - Coe, Christopher L; Rosenblum, Leonard A (Folia primatologica, 1978)
The physiological and behavioral factors underlying the annual reproductive cycle of the squirrel monkey were evaluated under controlled laboratory conditions. Mating activity following the formation of two social groups served to synchronize the reproductive phases during the subsequent year of observation. Changes in male and female reproductive status were assessed during four designated phases: breeding, pregnancy, lactation and fatting. Behavioral and somatic changes in gonadectomized subjects, living in the social groups, were also evaluated. The variations in behavior and physiology across the year were considered in terms of factors constraining the timing of the natural reproductive pattern.